Study of permeability changes induced by external stimuli on chemically modified electrodes - Perera, Dingiri Mudiyanselage Neluni T. (Kansas State University, 2010)
This research was focused on understanding how external stimuli affect the permeability of the chemically modified electrodes, and how the materials used in modifying the working electrodes respond to the changes in the surface charge. We adopted a voltammetric type electrochemical sensor to investigate the permeability effects induced by pH and organic solvents. The working electrodes used in this research were chemically modified with thioctic acid self assembled monolayer (TA SAM), track etched polycarbonate membranes (TEPCM) and PS-b-PMMA nanoporous films (polystyrene-block-polymethylmethacrylate). We studied the permeability behavior of each of the material upon application of external stimuli. In chapter 3, the permeability changes induced by change in surface charge of thioctic acid SAM was investigated. The surface charge of the monolayer was tuned by changing pH of the medium, which resulted in decrease of redox current of a negatively charged marker due to deprotonation of the surface –COOH groups of TA SAM. Decrease in redox current reflected a decrease in the reaction rate, and by using closed form equations the effective rate constants at several pKa values were extracted. In chapter 4, permeability changes induced by pH in TEPCM were investigated. We assessed the surface charge of these membranes via cyclic voltammetry generated for neutral and charged redox molecules. Limiting current of charged markers were affected by the surface charge induced by pH, where as the redox current for the neutral marker was not affected. Experimental redox currents were larger than the theoretical current, indicating that redox molecules preferentially distributed in a surface layer on the nanopore. Organic solvent induced permeability changes of PS-b-PMMA nanoporous films were investigated via electrochemical impedance spectroscopy and AFM. Higher response of pore resistance in the presence of organic solvents indicated either swelling of the nanoporous film or partitioning of organic solvents in the pores. However AFM data revealed that the permeability changes are due to partitioning of the solvents rather than swelling of the porous film, since there was no appreciable change if the pore diameter in the presence of solvents.
Keywords: nanomaterials, modified electrodes; electrochemistry; Chemistry, Analytical (0486)